The Development of Basic Mathematical Skills in Kindergarten 3 Children through Educational Game Activities from the Prodigy Math Website - นุชดอนไผ่ ทัศนีย์; เกตุแก้ว วลัยพรรณ; ผิวงาม รัตนชาติ; เทศปลื้ม มาริษา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this research are to: (1) examine the fundamental mathematical skills of kindergarten class level 1 children who experience learning through educational game activities from the Prodigy Math website, and (2) study the development of fundamental mathematical skills in these children after engaging with the educational game activities from the Prodigy Math website. The sample group consists of 15 kindergarten class level 3/3 at Ban Phaeo Kindergarten School (Wan Kru 2500), selected using cluster sampling. The research instruments include: (1) the educational game activity experience plan and (2) a fundamental mathematical skills test. Data analysis is conducted using mean, standard deviation, and relative gain score. The research results found that 1) after receiving an experience using educational game activities from the Prodigy Math website, early childhood had higher basic mathematics skills than before receiving the experience in every aspect, with one-to-one matching skills having the highest mean value (Mean = 9.13, S.D. = 1.25), followed by sequencing skills (Mean = 8.80, S.D. = 1.37), and classification skills (Mean = 7.87, S.D. = 2.00). The post-test scores were significantly higher than the pre-test scores at the .05 level of statistical significance. and 2) Early Childhood who participated in learning experiences using Prodigy Math games demonstrated a high overall development in fundamental mathematical skills, with a relative gain score of 73.86%.